What is next for CLIL Professional Development? - Jermaine S. McDougald (Universidad de La Sabana, 2020)
¿Qué sigue para el desarrollo profesional en AICLE? O que vem agora para o desenvolvimento profissional em CLIL? To reference this editorial (APA) / Para citar esta editorial (APA) / Para citar este editorial (APA) McDougald, J. (2019). What is next for CLIL professional development? Latin American Journal of Content & Language Integrated Learning, 12(2), 197-206. https://doi.org/10.5294/laclil.2019.12.2.1